2013
DOI: 10.1158/1078-0432.ccr-12-3363
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Midkine as a Diagnostic Serum Biomarker in Hepatocellular Carcinoma

Abstract: Purpose: To evaluate the value of serum midkine (MDK) as a diagnostic biomarker in hepatocellular carcinoma, particularly for those with negative alpha-fetoprotein (AFP) and at an early stage.Experimental Design: MDK expression in tumors was assessed by immunohistochemistry from 105 patients with hepatocellular carcinomas or liver cirrhosis. Serum MDK levels were detected by ELISA in 933 participants including hepatocellular carcinomas and hospital controls from different medical centers. Sensitivities and spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 39 publications
9
97
0
Order By: Relevance
“…In lung cancer patients, Ma et al showed that midkine mRNA level in peripheral blood mononuclear cells was significantly increased than that in groups of healthy volunteers and positively correlated with clinical stage, differentiated degree, and lymph node metastasis [16]. Zhu et al found that serum midkine levels were significantly elevated in hepatocellular cancer patients and significantly decreased in hepatocellular cancer patients after curative resection and re-increased when tumor recrudesced [29]. In addition, serum midkine had higher sensitivity for hepatocellular cancer diagnosis than AFP and had an outstanding performance in distinguishing AFP-negative hepatocellular cancers, early-stage hepatocellular cancers, and small hepatocellular cancers [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung cancer patients, Ma et al showed that midkine mRNA level in peripheral blood mononuclear cells was significantly increased than that in groups of healthy volunteers and positively correlated with clinical stage, differentiated degree, and lymph node metastasis [16]. Zhu et al found that serum midkine levels were significantly elevated in hepatocellular cancer patients and significantly decreased in hepatocellular cancer patients after curative resection and re-increased when tumor recrudesced [29]. In addition, serum midkine had higher sensitivity for hepatocellular cancer diagnosis than AFP and had an outstanding performance in distinguishing AFP-negative hepatocellular cancers, early-stage hepatocellular cancers, and small hepatocellular cancers [29].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al found that serum midkine levels were significantly elevated in hepatocellular cancer patients and significantly decreased in hepatocellular cancer patients after curative resection and re-increased when tumor recrudesced [29]. In addition, serum midkine had higher sensitivity for hepatocellular cancer diagnosis than AFP and had an outstanding performance in distinguishing AFP-negative hepatocellular cancers, early-stage hepatocellular cancers, and small hepatocellular cancers [29]. In breast cancer, although levels of serum midkine were increased in tumor tissues, there is no any association of serum midkine protein levels with clinical stage, tumor size, and lymph nodal status [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MDK can be used in the diagnosis of AFPnegative HCCs and very earlystages of HCCs. Furthermore, MDK can be used in HCC patients after curative resections to diagnose tumour recurrence [36] .…”
Section: Midkinementioning
confidence: 99%
“…Serum MDK as a biomarker in HCC diagnosis Published in 2013, a study that involved three independent cohorts with a total of 933 participants including 388 HCC cases and 545 different controls enrolled from different medical centers (78). Results showed that MDK levels were significantly elevated in HCC tissues as well as serum samples; serum MDK for HCC diagnosis showed an obviously higher sensitivity compared with AFP (86.9% vs.51.9%) with similar specificities (83.9% vs.86.3%); even in very early-stage HCC, the sensitivity of MDK is significant higher than AFP (80% vs. 40%); in those AFP-negative HCC cases, the sensitivity could reach as high as 89.2%; and serum MDK level was significantly decreased in HCC patients after curative resection and re-elevated when tumor relapsed.…”
Section: Research Advances In Other Serum Biomarkers For Early Hcc Dementioning
confidence: 99%